Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

simplify [ a-b,b-c,c-a]

Asked by 20th February 2009, 5:16 PM
Answered by Expert
Answer:

=( a-b) . ( (b-c) x (c-a) )

= (a-b) . ( b x c - b x a -c x c + c x a )

= (a-b) .( bxc + a x b +c x a)

=a.(b x c) +a.(ax b) + a. (c x a) - b. ( b x c) - b.(a x b) -b.(c x a)

= [ a b c] + 0 + 0 - 0 - 0 - [b c a]

=0

since [ a b c] = [b c a]

Answered by Expert 20th February 2009, 11:15 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!